Kepadatan Optimum dan Morfologi Spat Tiram Mutiara Pinctada maxima (Jameson) pada Pemeliharaan dengan Tingkat Kepadatan Berbeda - Tjahjo Winanto; Mohammad Djen Marasabessy; Safar Dodi (Journal Omni-Akuatika, 2016)
Stocking density was affected to the growth and survival rate of spat. The objective of this study is to obtain information optimal stocking density and morphology of spat during nursery culture. Randomized block design was applied with four stocking density treatments i.e. (A) 500, (B) 1000, (C) 1500, (D) 2000 individu (ind) collector-1,  conducted in triplcate The result showed that optimum density of P. maxima spat was 500 ind collector-1. The best of survival rate was found at density 500 ind collector-1 and the best of growth at treatment 500 ind collector-1 (36.50 x 33.37 mm). At the density of 500 ind collector1  shell morphology was normal, otherwise at high density (1,500 – 2,000 ind collector1) slower growth spat, shells shape is unnormal, for example  the shape of an elongated shell (DV> AP), or widened shape (DV <AP).